Desempenho agronômico a acúmulo de nutrientes pela planta de jambu - Souto, Gilberta Carneiro (Universidade Federal Rural do Semi-Árido, 2016)
Jambu is a species from the Northern region of Brazil, where it is widely used in food as a seasoning in typical regional dishes and in folk medicine. The objective of this work was to evaluate the effect of organic fertilizer doses on agronomic performance, nutrient accumulation gait and nutritional demand for jambu. The experiments were carried out in the didactic garden of the Federal Institute of Pará, campus Castanhal, during the periods of January and February of 2015 and of May and June of 2015, in soil classified as Yellow Latosol, dystrophic, of medium texture. The treatments consisted of the combination of two accessions of jambu (Purple Flower and Yellow Flower) and six doses of organic fertilizer (0, 2, 4, 6, 8, and 10 kg m-2). The experimental design was in randomized blocks, in a 2 x 6 factorial scheme, with four replications. The best agronomic performance of the jambu was obtained with the application of 10 kg m-2 of the organic fertilizer, with higher productivity in the cultivation carried out from May to June 2015. The access Yellow flower was more productive in relation to the Purple flower. The access Yellow flower was more productive in relation to the Purple flower. The decreasing order of nutrients accumulated by the jambu plant was potassium> nitrogen> calcium> magnesium> phosphorus, with period of higher growth and nutrient demand from 18 to 34 days after transplanting (DAT) for access 'Purple flower' and 26 To 42 DAT for 'Yellow Flower'
Agronomic performance to accumulation of nutrients by the jambu plant
Keywords: Acmella oleracea[(L.)R. K. Jansen]; Compostagem; Nutrição de plantas; (Acmella oleracea[(L.)R. K. Jansen]; Composting; Nutrition of plants; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA